Guanylate Binding Proteins Restrict Leishmania donovani Growth in Nonphagocytic Cells Independent of Parasitophorous Vacuolar Targeting - Haldar, Arun Kumar (mBio, 2020)
Interferon (IFN)-inducible guanylate binding proteins (GBPs) play important roles in host defense against many intracellular pathogens that reside within pathogen-containing vacuoles (PVs). For instance, members of the GBP family translocate to PVs occupied by the protozoan pathogen Toxoplasma and facilitate PV disruption and lytic parasite killing. While the GBP defense program targeting Toxoplasma has been studied in some detail, the role of GBPs in host defense to other protozoan pathogens is poorly characterized. Here, we report a critical role for both mouse and human GBPs in the cell-autonomous immune response against the vector-borne parasite Leishmania donovani. Although L. donovani can infect both phagocytic and nonphagocytic cells, it predominantly replicates inside professional phagocytes. The underlying basis for this cell type tropism is unclear. Here, we demonstrate that GBPs restrict growth of L. donovani in both mouse and human nonphagocytic cells. GBP-mediated restriction of L. donovani replication occurs via a noncanonical pathway that operates independent of detectable translocation of GBPs to L. donovan-containing vacuoles (LCVs). Instead of promoting the lytic destruction of PVs, as reported for GBP-mediated killing of Toxoplasma in phagocytic cells, GBPs facilitate the delivery of L. donovani into autolysosomal-marker-positive compartments in mouse embryonic fibroblasts as well as the human epithelial cell line A549. Together our results show that GBPs control a novel cell-autonomous host defense program, which renders nonphagocytic cells nonpermissible for efficient Leishmania replication.